Biliary strictures complicating liver transplantation in pediatric patients: Experience in a South American transplant center (2017)
To describe the experience of percutaneous transhepatic cholangiography (PTC) with biliary dilatation and drainage after pediatric liver transplantation and to determine the long-term outcome of this procedure. Methods: Retrospective study from 2001 to 2013. Follow-up after treatment was also undertaken. A survival analysis was performed in patients in whom the procedure and eventual removal of the catheter were successful. Results: In all, 196 children received liver transplants; 40 of them (20 boys and 20 girls; median age of 4 years) were treated using PTC due to biliary complications. Sixty-one PTC procedures were performed in 40 liver transplant recipients. Technically successful PTC was achieved in 87.5% of the patients. The probability of a patient not developing unfavorable outcomes 1, 5, and 10 years after treatment was 88.9%, 83.0%, and 74.1%.